Peran Dinas Perhubungan Kabupaten Cilacap Dalam Pembinaan Juru Parkir Di Wilayah Kota Cilacap - Wahyu Hariadi; haris kusuma wardana haris; Agoes Djatmiko (Wijayakusuma Law Review, 2024)
Parking is one of the components or inseparable aspects of the needs of the transportation system, because every trip by private vehicle generally always starts and ends at the parking lot. Basically parking is a public need that initially functions to serve. In accordance with this function, parking space is adjusted according to demand in line with the needs of people who drive to be in or access a place. Regarding parking, it has been regulated in Article 1 of Law Number 22 of 2009 concerning Road Traffic and Transportation, which reads: "Parking is when the vehicle stops or does not move for a while and is left by the driver. Problems arise when Parking Guidance and Determination of Parking Facilities are not carried out properly, this is where the government is required to be able to solve existing problems, to fulfill these objectives through Cilacap district regional regulation no. 6 of 2018 concerning the implementation of transportation, Article 26, Article 27 and Article 35, it is hoped that the Cilacap Regency Transportation Service can work optimally in its implementation. Coaching is a process, manufacture, method of coaching, renewal, efforts and actions or activities carried out in an efficient and effective manner. The approach method in this study is the approach method used in the research is normative juridical, namely an approach that uses a positivist-legislative conception. The concept of positivist legislature is written norms made and promulgated by authorized officials and views law as a normative system that is independent, closed and detached from real community life